The Use of Artificial Intelligence in Personalizing Learning Experiences at Schools - Febrianti, Cindi; Tari, Kartika Januan; Ariska, Yeli; Lestari, Reni (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
The implementation of personalized learning often faces obstacles, especially related to the workload of teachers who have to manage the learning needs of many students simultaneously. In this situation, AI comes as an innovative solution. This study uses a literature review approach to explore the use of Artificial Intelligence (AI) in personalizing learning experiences in schools. Literature review was chosen as the main method because it allows researchers to analyze and synthesize various previous studies, both theoretical and empirical, in order to build a comprehensive understanding. Data in this study were collected through a systematic review of secondary sources, including journal articles, books, research reports, and policy documents related to the use of AI in education. Literature searches were conducted using academic databases such as Google Scholar, ScienceDirect, Springer, and ProQuest, with relevant keywords such as “Artificial Intelligence in Education”, “Personalized Learning with AI”, and “Educational Technology Implementation”. This study found that AI has great potential to improve the personalization of learning experiences in schools. With its ability to analyze student data in real-time, AI can provide learning experiences that are tailored to individual needs, learning styles, and levels of understanding. This allows teachers to identify areas that require special attention and provide relevant materials, accelerate the learning process, and improve academic outcomes. To support the implementation of AI in education, clear policies are needed and training support for teachers is needed so that they can make optimal use of this technology. In addition, investment in adequate technological infrastructure is also very important so that AI can be effectively integrated into the learning process. Collaboration between the government, educational institutions, and technology parties is key to achieving this goal.